2013
DOI: 10.1155/2013/284780
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in Australian Hospitals: A Prospective Study

Abstract: Objectives. Australian data regarding delirium in older hospitalized patients are limited. Hence, this study aimed to determine the prevalence and incidence of delirium among older patients admitted to Australian hospitals and assess associated outcomes. Method. A prospective observational study (n = 493) of patients aged ≥70 years admitted to four Australian hospitals was undertaken. Trained research nurses completed comprehensive geriatric assessments using standardized instruments including the Confusion As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…A prevalence survey in Ireland found just 43.6% of patients with delirium had confusion noted by medical staff though overall prevalence of undiagnosed delirium was similar (Ryan et al, ). Frequency of any delirium in point prevalence surveys of older hospital inpatients was also comparable to other recent studies ranging from 17.3%–19.1% (Gonzalez Pezoa et al, ; Ryan et al, ; Travers et al, ; Wand et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…A prevalence survey in Ireland found just 43.6% of patients with delirium had confusion noted by medical staff though overall prevalence of undiagnosed delirium was similar (Ryan et al, ). Frequency of any delirium in point prevalence surveys of older hospital inpatients was also comparable to other recent studies ranging from 17.3%–19.1% (Gonzalez Pezoa et al, ; Ryan et al, ; Travers et al, ; Wand et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In the hospitalised elderly, the reported incidence of delirium may be as high as 50% (Inouye et al, ). Delirium superimposed on dementia is particularly prevalent (Travers et al, ; Wand et al, ; Fong et al, ). A recent review reported that dementia was a significant risk factor for delirium in hospitalised elderly patients; the presence of dementia at baseline consistently increased the risk of delirium between two to five times, with delirium rates between 9 and 44% (Fong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is a serious medical condition with a prevalence of approximately 15% among hospitalized older adults . It is more common in the critically ill and in those undergoing major surgery, such as cardiac surgery, where estimates of prevalence can reach up to 42% …”
Section: Summary Of Clinical Trials Investigating Role Of Melatonin Omentioning
confidence: 99%
“…D elirium is a serious medical condition with a prevalence of approximately 15% among hospitalized older adults. 1 It is more common in the critically ill and in those undergoing major surgery, such as cardiac surgery, where estimates of prevalence can reach up to 42%. [2][3][4][5] Current approaches to the prevention of delirium in hospitalized patients include both nonpharmacologic and pharmacologic approaches.…”
mentioning
confidence: 99%